Emergence of Private Higher Education in Algeria: Actors and Pathways - Bedaida Imad Eddine; Benguerna Mohamed; Meyer Jean-Baptiste (Economics and Business)
Since gaining independence, the higher education sector in Algeria has undergone several reforms to fulfil the country’s requirements in terms of higher education, both to absorb the growing number of high-school graduates and meet the needs of the labour market. The emergence of a private higher education sector in Algeria has been slow in comparison to European countries, the United States, Japan and our culturally/historically-similar neighbouring countries (Tunisia and Morocco). This article reveals the results of research conducted on the context, governance and development of private higher education in Algeria. To achieve the objectives of our research, the study was conducted on five recently-accredited private higher education institutions through field observation, documentary analysis and interviews with executives, teachers and students at these institutions. The main results of the qualitative research suggest that private higher education continues to evolve through a transitional phase characterised by a gradual integration into the socio-economic framework of the country. Through these results, we contribute firstly on a theoretical and academic level by conducting the first research on the private sector of higher education in Algeria; secondly, on a practical level, by providing a clear and comprehensive view of the situation of the emerging private sector in Algeria.